THE INFLUENCE OF CLOUD ACCOUNTING APPLICATIONS ON THE ACCOUNTING AND AUDITING PROFESSION IN IRAQ - Asaad Mohammed Ali Wahhab; Azher Subhi Abdulhussein; Mushtaq Talib Abdulameer Al-Shammar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The present study aims to identify the important role of cloud accounting applications in Iraqi small, medium and large companies in the future and their influence on the accounting and auditing profession. The research problem was represented by the following questions: Do cloud accounting applications in small, medium, and large companies affect the accounting profession in Iraq ?? Do cloud accounting applications in small, medium, and large companies affect the profession of auditing in Iraq ?? The researchers have found the weakness of the skills of Iraqi internal auditors in accounting Electronic systems. The Iraqi companies lack the basic components for the application of cloud accounting.